Holocene dynamics of tree taxa populations in Italy - Magri, Donatella; Agrillo, Emiliano; Di Rita, Federico; Furlanetto, Giulia; Pini, Roberta; Ravazzi, Cesare; Spada, Francesco (Review of Palaeobotany and Palynology, 2014)
The Holocene distribution of nine tree taxa (Picea, Abies, Betula, Fagus, Carpinus betulus, Corylus, deciduous and evergreen Quercus, and Olea) in Italy is visually shown by pollen maps. A hundred pollen sites were selected, percentageswere derived fromthe original pollen counts or digitized frompublished diagrams, and represented on maps in subsequent time windows at 1000-year intervals. The pollen maps depict the Holocene history of Italian forest cover as a complex puzzle influenced by very diverse climate, physiography, edaphic and ecological processes, and a long history of human activity. A reasonably goodmatch between the abundance and distribution of pollen data during the last thousand years and the current tree species distribution in Italy indicates that the Holocene pollen maps may represent a fundamental basis for a better understanding of the modern vegetation patterns, often showing discontinuous ranges and complex distributions. Although clear latitudinal gradientswere not detected, regions characterized by high precipitation values hosted dense forest cover since the Holocene onset, while areas with arid climate experienced a delayed increase in trees and a faster decrease during the last four millennia. Fagus, C. betulus and Picea showdisplacement in their distribution inItaly in the course of theHolocene.Other taxa, likedeciduous and evergreen Quercus, and Betula have always occupied the same locations during the Holocene, but show changes in abundance. Abies had a broken distribution in Italy throughout the postglacial. Its populations are currently found within the regions they occupied at the onset of the Holocene. The importance of considering all the available records in their geographical context to reconstruct complex vegetational patterns is discussed.
Keywords: Database; Holocene; Italy; Pollen map; Woody taxon

Rapid climatic changes and resilient vegetation during the Lateglacial and Holocene in a continental region of south-western Europe - Aranbarri, Josu; González-Sampériz, Penélope; Valero-Garcés, Blas; Moreno, Ana; Gil-Romera, Graciela; Sevilla-Callejo, Miguel; García-Prieto, Eduardo; Di Rita, Federico; Mata, M. Pilar; Morellón, Mario; Magri, Donatella; Rodríguez-Lázaro, Julio; et al. (Global and Planetary Change, 2014)
Palynological, sedimentological and geochemical analyses performed on the Villarquemado paleolake sequence (987m a.s.l, 40°30′N; 1°18′W) reveal the vegetation dynamics and climate variability in continental Iberia over the last 13,500calyrBP. The Lateglacial and early Holocene periods are characterized by arid conditions with a stable landscape dominated by pinewoods and steppe until ca. 7780calyrBP, despite sedimentological evidence for large paleohydrological fluctuations in the paleolake. The most humid phase occurred between ca. 7780 and 5000calyrBP and was characterized by the maximum spread of mesophytes (e.g., Betula, Corylus, Quercus faginea type), the expansion of a mixed Mediterranean oak woodland with evergreen Quercus as dominant forest communities and more frequent higher lake level periods. The return of a dense pinewood synchronous with the depletion of mesophytes characterizes the mid-late Holocene transition (ca. 5000calyrBP) most likely as a consequence of an increasing aridity that coincides with the reappearance of a shallow, carbonate wetland environment. The paleohydrological and vegetation evolution shows similarities with other continental Mediterranean areas of Iberia and demonstrates a marked resilience of terrestrial vegetation and gradual responses to millennial-scale climate fluctuations. Human impact is negligible until the Ibero-Roman period (ca. 2500calyrBP) when a major deforestation occurred in the nearby pine forest. The last 1500years are characterized by increasing landscape management, mainly associated with grazing practices shaping the current landscape.
Keywords: aridity; Continental Iberia; Holocene; Multiproxy reconstructio; Pinewoods; Vegetation resilience

The cultural landscape near the ancient city of Tharros (central West Sardinia): vegetation changes and human impact - Di Rita, Federico; Melis, Rita Teresa (Journal of Archaeological Science, 2013)
The evolution of the cultural landscape in coastal western Sardinia is investigated by means of pollen analysis in the Mistras Lagoon sediments, near the ancient city of Tharros, with particular attention to changes in evergreen vegetation and the impact of human activity. The pollen diagram, spanning the time interval from 5300 to 1600 cal BP, documents the influence of man, climate, and geomorphic dynamics and on the evolution of a semi-open evergreen vegetation landscape and variations in extent of a salt-marsh environment. Anthropogenic indicators and microcharcoals concur in depicting increased land use coinciding with the Nuragic, Phoenician, Punic and Roman dominations. Pollen data, along with archaeobotanical evidence, suggest a prevailing arable farming economy, vocated to Vitis and cereals expoitation, during the Nuragic phase until 2400 cal BP, replaced since then by a prevailing stock rearing economy. Between 2050 and 1600 cal BP, a less intensive human impact on the landscape is profiled, consistently with the archaeologically documented abandonment of the rural villages in favour of a slow urbanization, experienced by the Sinis territory in Imperial times. The pollen record provides new insights into the history of important economic plants in the Mediterranean, such as Vitis, Olea and Quercus suber. The results of the pollen analysis reveal how the records of these taxa are primarily influenced by the cultural development of the Sinis region and secondarily by dynamics involving the natural companion vegetation.
The following values have no corresponding Zotero field: publisher: Elsevier Ltd
Keywords: evergreen vegetation; Holocene; human impact; pollen; Sardinia

A Lateglacial and early Holocene pollen record from Valle di Castiglione (Rome): Vegetation dynamics and climate implications - Di Rita, Federico; Anzidei, Anna Paola; Magri, Donatella (Quaternary International, 2013)
A new pollen record from Valle di Castiglione near Rome (core VdC09) has been studied with the aim of providing a detailed reconstruction of the vegetation history of the Roman landscape between 13,800 and 7700 cal BP, in response to the Lateglacial and early Holocene climate events. An open landscape dominated by steppe vegetation characterized the Lateglacial, so that only a modest increase of trees took place during the Allerød interstadial. The Intra Allerød Cold Period induced instability in the development of the woody communities. The Holocene forest recovery started around 11,600 cal BP, but definite forest development occurred only around 11,100 cal BP, at the end of the Preboreal Oscillation, which produced an important re-expansion of herbs. The evergreen Mediterranean vegetation was constantly present in the landscape, even during the Lateglacial cold fluctuations. A clear early Holocene increase in evergreen trees corresponds to the attainment of high and stable values in the GISP2 δ18O curve, around 10,200 cal BP.
The following values have no corresponding Zotero field: publisher: Elsevier Ltd and INQUA
Keywords: climate changes; deciduous and evergreen forests; Holocene; landscape (voyant); Mediterranean Region; Pollen analysis; Vegetation dynamics

Holocene environmental instability in the wetland north of the Tiber delta (Rome, Italy): sea-lake-man interactions - Di Rita, Federico; Celant, Alessandra; Magri, Donatella (JOURNAL OF PALEOLIMNOLOGY, 2010)
Combined analyses of pollen, seeds, woods, micro-charcoal and non-pollen palynomorphs from Stagno di Maccarese, an artificially dried out coastal basin north of the Tiber delta now occupied by the Fiumicino Airport (Rome, Italy), document marked vegetation and environmental changes during the last 8300 years. Between 8300 and 5400 cal. a BP dense mixed deciduous and evergreen forests surrounded a eutrophic freshwater basin. An abrupt change around 5400 cal. a BP marks the transition to a marshy environment, due to a lowering of the water table. An increase of cereals and micro-charcoals matches the presence of a nearby Eneolithic settlement. Between 5100 and 2900 cal. a BP there is a remarkable expansion of riparian trees, indicating an increase of the water level. Between 2900 and 2000 cal. a BP, a new development of marshlands points to a progressive lowering of the lake. After 2000 cal. a BP, during the Roman exploitation of the area, an expansion of arboreal vegetation is recorded, characterized by evergreen and deciduous oak-dominated forests, while an extensive chenopods marshland matches the presence of saltworks. On the whole, the Stagno di Maccarese area appears very unstable, due to changes in lake level, introgression of marine water, eutrophic phases, flood events, desiccations and openings of the forest vegetation.
The following values have no corresponding Zotero field: pub-location: VAN GODEWIJCKSTRAAT 30, 3311 GZ DORDRECHT, NETHERLANDS publisher: SPRINGER
Keywords: Hydrological changes; Plant macrofossils; Pollen analysis; Saltworks; Tiber delta